Coupled rheological behavior of tunnel rock masses reinforced by rock bolts based on the non-hydrostatic stress field. (July 2023) - Wang, Gang; Fang, Wei; Han, Wei; Jiang, Yujing; Zhang, Xianda; Xu, Feng; Zhang, Shubo
Highlights: The viscoelastic behavior for rock mass of a circular tunnel supported with rock bolts was studied. Focus on the distribution of rock mass stress and displacement of the coupled rheological model. Discuss the coupled behavior of rock mass-rock bolts under a non-hydrostatic stress field. Abstract: The stress and deformation characteristics of the rock mass and the rock bolt reinforcement structure change over time, as a result, it is of significance to understand the coupled rheological behavior of these two systems. In this paper, we first develop viscoelastic solutions for the rock mass reinforced by rock bolts under non-hydrostatic stresses based on the distributed force model. Subsequently, the Maxwell-Maxwell (M−M) and the Maxwell-Burgers (M−B) constitutive models are applied to the rock bolts and the rock mass, respectively, and the corresponding viscoelastic analytical solutions are then obtained. Finally, the numerical software FLAC 3D is used to verify the fidelity of the mechanistic model. Our results show that the lateral pressure coefficient is positively correlated with the radial stress and the radial displacement. The radial stress in the rock mass reaches a stable value with time. Furthermore, the lateral pressure coefficient has a positive correlation with the axial force in the rock bolts in elastic analysis. However, as the creep in the rock mass develops, the axial forces under different lateral pressure coefficients gradually reach a stable value. Moreover, the lateral pressure coefficient mainly affects the distribution of axial force and the slope of the axial force in the rock bolts.